Impulse Oscillometry as a measure of airway dysfunction in Sarcoidosis - Bade, Geetanjali; Akhtar, Nasim; Trivedi, Anjali; Madan, Karan; Guleria, Randeep; Talwar, Anjana (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2021)
Background: Sarcoidosis is a systemic inflammatory granulomatous disease which commonly affects intrathoracic lymph nodes, lung parenchyma and airways.Objectives: To perform spirometry and measure respiratory impedance using impulse oscillometry in sarcoidosis patients and compare the parameters with healthy controls.Methods: Patients having stage I and II Sarcoidosis (n=28); and age and gender matched healthy controls (n=17) were recruited. Lung volumes and capacities were measured by spirometry and respiratory system impedance was assessed using Impulse oscillometry system (IOS). Measurements were performed before and 15 minutes after inhalation of a short acting bronchodilator. The IOS and spirometric parameters were compared between two groups and correlated. ROC analysis was also performed to identify the IOS parameters which can discriminate between sarcoidosis and healthy controls.Results: Resistance at 5 and 20 Hz (R5 and R20), reactance at 5 and 20 Hz (X5 and X20), small airway resistance (R5-R20), resonant frequency (FRes) and area of reactance (AX) were significantly higher in sarcoidosis as compared to the control group. Forced expiratory volume in 1 second [FEV1(% predicted)] and forced vital capacity [FVC (% predicted)] were significantly lower in patients with sarcoidosis than controls. while FEV1/FVC ratio and peak expiratory flow rate (PEF) values were comparable between patients and healthy controls. Post bronchodilator inhalation, there was reduction in airway resistance and reactance, but no significant changes occurred in spirometric parameters. R5, R5-R20, AX and FRes demonstrated significant negative correlation with FEV1.Conclusion: Significantly increased airway resistance and reactance were observed in sarcoidosis patients as compared to controls.